Advances in auxin synthesis, transport, and signaling in rice: implications for stress resilience and crop improvement - Hou, Mengmeng; Zhang, Yuanbo; Xu, Xinyi; Ai, Hao (Frontiers in Plant Science, 2025)
Auxin, a crucial plant hormone, plays a pivotal role in regulating various aspects of rice growth and development, including cell elongation, root formation, and responses to environmental stimuli. Recent breakthroughs in auxin research have revealed novel regulatory mechanisms, such as the identification of auxin-related genes like DNR1 and OsARF18, which enhance rice nitrogen use efficience and resistance to glufosinate. Additionally, advancements in understanding auxin transport and signaling pathways have highlighted their potential in optimizing tillering, root architecture, and grain yield. This review examines these molecular mechanisms and their interactions with other hormones, emphasizing their integration into breeding programs for improved rice productivity. By synthesizing these findings, we provide a comprehensive overview of how auxin research informs strategies for developing rice varieties with enhanced adaptability and optimized growth, contributing to food security and sustainable agriculture.